Evolution and maintenance of haploid–diploid life cycles in natural populations: The case of the marine brown alga Ectocarpus. (15th July 2015) - Couceiro, Lucía; Le Gac, Mickael; Hunsperger, Heather M.; Mauger, Stéphane; Destombe, Christophe; Cock, J. Mark; Ahmed, Sophia; Coelho, Susana M.; Valero, Myriam; Peters, Akira F.
<x xml:space="preserve">Abstract</x> The evolutionary stability of haploid–diploid life cycles is still controversial. Mathematical models indicate that niche differences between ploidy phases may be a necessary condition for the evolution and maintenance of these life cycles. Nevertheless, experimental support for this prediction remains elusive. In the present work, we explored this hypothesis in natural populations of the brown alga Ectocarpus. Consistent with the life cycle described in culture, Ectocarpus crouaniorum in NW France and E. siliculosus in SW Italy exhibited an alternation between haploid gametophytes and diploid sporophytes. Our field data invalidated, however, the long‐standing view of an isomorphic alternation of generations. Gametophytes and sporophytes displayed marked differences in size and, conforming to theoretical predictions, occupied different spatiotemporal niches. Gametophytes were found almost exclusively on the alga Scytosiphon lomentaria during spring whereas sporophytes were present year‐round on abiotic substrata. Paradoxically, E. siliculosus in NW France exhibited similar habitat usage despite the absence of alternation of ploidy phases. Diploid sporophytes grew both epilithically and epiphytically, and this mainly asexual population gained the same ecological advantage postulated for haploid–diploid populations. Consequently, an ecological interpretation of the niche differences between haploid and diploid individuals does not seem to satisfactorily explain the evolution of the Ectocarpus life cycle.